(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To assess the articles published on current and recent advanced treatments of premature ejaculation (PE) and assist clinicians to select the effective management of PE by increasing knowledge and awareness of the outcomes associated with current medical and surgical treatment options. Methods: An Online literature search was conducted to identify relevant, peer-reviewed, and clinical and review articles published related to current and recent advanced treatments of premature ejaculation (PE). Search terms for this non-systematic review included ‘premature ejaculation’, ‘current treatment and outcome’, ‘new development of Premature Ejaculation’. Search terms were separately searched and in combination. Case studies and editorials were excluded. Primary manuscripts and reviews were included and references of articles of interest were reviewed and key references were obtained. Result: There is no established treatment, validated screening instrument or diagnostic criteria for PE. The pathophysiology and etiology of PE are not well known. The negligence of patients and physicians to talk about PE and the lack of knowledge are the main barrier for the treatment of PE. Currently there are several treatment options including psychological counseling, behavioral therapy, and pharmacotherapy like antidepressants, topical anesthetics or phosphodiesterase-5 inhibitor. However, surgical treatment remains on trial, specifically dorsal nerve division. Bangladesh Journal of Urology, Vol. 20, No. 1, January 2017 p.42-45